Ceratothoa oestroides Infection in European Sea Bass: Revealing a Long Misunderstood Relationship - Piazzon, M. Carla; Mladineo, Ivona; Dirks, Ron P.; Santidrián Yebra-Pimentel, Elena; Hrabar, Jerko; Sitjà-Bobadilla, Ariadna (Frontiers in Immunology, 2021)
Ceratothoa oestroides (Cymothoidea, Isopoda) is a generalist crustacean parasite that negatively affects the economic sustainability of European sea bass (Dicentrarchus labrax) aquaculture in the North-East Mediterranean. While mortalities are observed in fry and fingerlings, infection in juvenile and adult fish result in approximately 20% growth delay. A transcriptomic analysis (PCR array, RNA-Seq) was performed on organs (tongue, spleen, head kidney, and liver) from infected vs. Ceratothoa-free sea bass fingerlings. Activation of local and systemic immune responses was detected, particularly in the spleen, characterized by the upregulation of cytokines (also in the tongue), a general reshaping of the immunoglobulin (Ig) response and suppression of T-cell mediated responses. Interestingly, starvation and iron transport and metabolism genes were strongly downregulated, suggesting that the parasite feeding strategy is not likely hematophagous. The regulation of genes related to growth impairment and starvation supported the growth delay observed in infected animals. Most differentially expressed (DE) transcripts were exclusive of a specific organ; however, only in the tongue, the difference between infected and uninfected fish was significant. At the attachment/feeding site, the pathways involved in muscle contraction and intercellular junction were the most upregulated, whereas the pathways involved in fibrosis (extracellular matrix organization, collagen formation, and biosynthesis) were downregulated. These results suggest that parasite-inflicted damage is successfully mitigated by the host and characterized by regenerative processes that prevail over the reparative ones.